Repeated Signaling and Firm Dynamics - Hennessy, Christopher A.; Livdan, Dmitry; Miranda, Bruno (Review of Financial Studies, 2010)
As an alternative to the pecking order, we develop a dynamic calibratable model where the firm avoids mispricing via signaling. The model is rich, featuring endogenous invest-ment, debt, default, dividends, equity flotations, and share repurchases. In equilibrium, firms with negative private information have negative leverage, issue equity, and overin-vest. Firms signal positive information by substituting debt for equity. Default costs induce such firms to underinvest. Model simulations reveal that repeated signaling can account for countercyclical leverage, leverage persistence, volatile procylical investment, and correla-tion between size and leverage. The model generates other novel predictions. Investment rates are the key predictor of abnormal announcement returns in simulated data, with lever-age only predicting returns unconditionally. Firms facing asymmetric information actually exhibit higher mean Q ratios and investment rates. (JEL G32) Three decades have passed since Leland and Pyle (1977) and Ross (1977) de-veloped the signaling theory of corporate finance. Although their work has been extended, signaling models remain static and qualitative, making it im-possible for empiricists to assess the theory’s ability to match observed time-